Production practice, market and value chain study of organic apple of Jumla - Atreya, PN; Kafle, A (Journal of Agriculture and Environment, 2018)
This study was undertaken to explore the market and value chain of apple in Jumla and Nepaljung in January 2014. Primary and secondary data were used for this study. All together 10 respondent farmers were selected for production related data, five retailers from Jumla and Nepaljung, one wholesaler from Nepaljung and 10 consumers for market study. Highest wholesale price was observed in May/June - June/July (NRs. 145/kg) while lowest was in Sept./Oct.-Oct./Nov. (NRs. 83/kg). Similarly highest retail price (NRs. 185/kg) was in the month of June/July and lowest (NRs. 115/Kg) was in Sept./Oct-Oct./Nov. The average farm gate price of apple is too low (NRs.26.93/kg) as compared to wholesale, retail and consumers prices. The producers, traders, transporters, wholesalers and retailers were the main marketing actors of apple. Contractual system before and during production were observed in marketing. Price spread of Jumla apple was assessed with the different actors (contractors, traders, wholesalers, retailers and consumers) in value chain. Apple is the major commodity for income generation so better knowledge on production marketing and value addition through processing should be imparted to the farmers.